The effect of voluntary participation on cooperation - Daniele Nosenzo; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
We study the effects of voluntary participation on cooperation in collective action problems. Voluntary participation may foster cooperation through a mechanism of assortative selection of interaction partners based on false consensus bias, or through a mechanism whereby the decision to not participate can be used as a threat against free-riders. We examine the effectiveness of these mechanisms in a one-shot public goods experiment. Voluntary participation has a positive effect on provision only through the threat of non-participation. Assortative selection of interaction partners seems to play a minor role in our setting, whereas the threat of non-participation is a powerful force to discipline free-riding.
Keywords: C91; D02; H41; 330; collective action; cooperation; voluntary participation; experiment